PENGARUH PEMBERIAN AIR SUSU IBU (ASI), KONSUMSI ZAT GIZI, DAN KELENGKAPAN KARTU MENUJU SEHAT (KMS) TERHADAP STATUS GIZI BAYI - Suci Pujiyanti (Food and Nutrition Society of Indonesia, 2008)
Breastfeeding, nutrition consumption, and completeness of healthy card (KMS) are very crucial to support infant development. The objective of this research was to analyze the effect of breastfeeding, nutrition consumption, and completeness of healthy card to the nutritional status. Sample of babies who breastfed and having KMS were taken from 50 babies aged around 4-12 months using a simple random sampling method. Pearson corelation, Spearman corelation, and backward linear regression were used to analyze data. Linear regression analysis between the length of breastfeeding (p<0.01) and sufficiency of protein level (p<0.01) showed impact significantly to the infant nutritional status. The level energy sufficiency did not affect (p>0.05) the infant nutritional status. The analysis also showed effect of weighing, immunization, and giving vitamin A to infant nutritional status.